2013
DOI: 10.3892/ol.2013.1196
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DNA-PKcs and BRCA1 as prognostic indicators in nasopharyngeal carcinoma following intensity-modulated radiation therapy

Abstract: The mechanisms of radiation-induced effects in cancer mainly involve double-strand breaks (DSBs) which are important in maintaining the stability of genes. The DNA repair genes breast cancer 1 (BRCA1) and DNA-dependent protein kinase catalytic subunit (DNA-PKcs) are capable of maintaining genetic stability through two distinct and complementary repair mechanisms for DNA DSBs, known as repair-homologous recombination (HR) and non-homologous end joining (NHEJ). DNA-PKcs is a member of the phosphatidylinositol 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…We identified additional DNA repair factors, notably BRCA1 and DNA-PKcs which were significantly upregulated basally in A549 CD133+ cells and could also serve as promising CSC specific therapeutic targets. While their targeting has been proposed in multiple cancer models, their efficacy in inducing radiosensitivity in CSCs has largely yet to be explored [3133]. …”
Section: Discussionmentioning
confidence: 99%
“…We identified additional DNA repair factors, notably BRCA1 and DNA-PKcs which were significantly upregulated basally in A549 CD133+ cells and could also serve as promising CSC specific therapeutic targets. While their targeting has been proposed in multiple cancer models, their efficacy in inducing radiosensitivity in CSCs has largely yet to be explored [3133]. …”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that decreased DNA-PKcs expression can also drive tumor progression. Breast cancer patients with lower DNA-PKcs levels tended to have a higher rate of distant metastases and poorer prognosis [ 181 ]. The DNA-PKcs activity in the PBLs of patients with advanced cancer was determined to be significantly lower than in patients at an earlier cancer stage, and those patients had lower rates of disease free and distant metastasis free survival [ 182 ].…”
Section: Core Nhej Factors In Carcinogenesis and Cancermentioning
confidence: 99%
“…Ku80 is overexpressed in half of all HNSCC tumors analyzed in a study Moeller, B.J., et al, and it was found to be an independent predictor for both locoregional failure and mortality following radiotherapy [ 193 ]. Increased DNA-PKcs expression predicted poor outcome in nasopharyngeal carcinoma patients undergoing intensity modulated radiation therapy (IMRT), independent of classical markers [ 181 ]. DNA-PKcs also promotes radiation resistance in cervical and breast cancers as well as correlating with radioresistance in lung cancer lines [ 194 , 195 , 196 ].…”
Section: Core Nhej Factors In Carcinogenesis and Cancermentioning
confidence: 99%
“…Enhanced DNA repair activity tends to be resistant to radiotherapy. DNA-dependent protein kinase catalytic subunit (DNA-PKcs) and ataxia telangiectasia-mutated are two members of the PI3K family that repair DNA DSBs (97)(98)(99). Inhibition of PI3 kinases using a pharmacological approach may improve the response of cancer cells to radiotherapy.…”
Section: Pi3k/akt and The Cell Cycle In Radiation Resistancementioning
confidence: 99%